Comparison of the outcomes between laparoscopic totally extraperitoneal repair and prolene hernia system for inguinal hernia; review of one surgeon's experience - Choi, Yoon Young (The Korean Surgical Society, 2012)
PURPOSE: To compare the outcomes between laparoscopic total extraperitoneal (TEP) repair and prolene hernia system (PHS) repair for inguinal hernia. METHODS: A retrospective analysis of 237 patients scheduled for laparoscopic TEP or PHS repair of groin hernia from 2005 to 2009 was performed. RESULTS: The mean age was 52.3 years in TEP group and 55.7 years in PHS group. Of 119 TEP cases, 98 were indirect inguinal hernia, 15 direct type, 5 femoral hernia and 1 complex hernia; Of 118 PHS cases, 100 indirect, 18 direct type. All in TEP group were performed under general anesthesia and 64% of PHS group were performed under spinal or epidural anesthesia. Preoperatively, 10 cases of recurrent inguinal hernia were involved in our study (4 in TEP, 6 in PHS group). The mean operative time was similar in both groups (74.8 in TEP, 71.2 in PHS group), however mean hospital stay (1.6 days in TEP, 3.2 days in PHS group, P = 0.018) and mean usage of analgesics (0.54 times in TEP, 2.03 times in PHS group, P < 0.01), complications (36 cases in TEP, 6 cases in PHS group, P < 0.01) showed statistical differences. There is only 1 case of postoperative recurrence inguinal hernia in PHS group but it has no statistical significance (P = 0.314). CONCLUSION: Compared to PHS repair, laparoscopic TEP repair has some advantages; shorter hospital stay, less frequent need of analgesics; as well as more postoperative complications such as hematoma, seroma, scrotal swelling.